Tinjauan Terhadap Sistem Layanan Sirkulasi di Kantor Arsip, Perpustakaan, dan Dokumentasi Kota Padang - Yurdanis, Yurdanis; Delman, Delman (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
According to analysis carried out through observation and interviews show that: (1)Office of Archives, Library and Documentation services the city of Padang in applying open systems or open accses not run according to proper service which allows users to search for library services directly to its line of book shelf library. However, upon return visitor instantly put on the shelf book, (2) the constraints faced by the Office of Archives, Library and Documentation of Padang is still a lack of socialization or disciplinary rules as guidance literature. In addition,the existing infrastructure in the Office of Archives, Library and Documentation of Padang is still not adequate as the lack of computers and inadequate space, causing less users feel comfortable in the Office of Archives, Library and Documentation Padang. Keywords: open access; library service